PENGARUH DUKUNGAN ORANG TUA TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA KELAS V SD INPRES 48 KABUPATEN SORONG - Lani Indriyani; Nurul; Kukuh Arif Styawati; Ristin Muharomah; Siti Fatimah Az-Zahra; Oki Sandra Agnesa (STKIP Subang, 2026)
This study aims to analyze the effect of parental guidance on the learning outcomes of fifth-grade students at SD Inpres 48 Kabupaten Sorong. Parental guidance is defined as intentional and consistent support provided by parents encompassing academic assistance, emotional encouragement, discipline reinforcement, and creation of a conducive home learning environment. This research employs a quantitative approach with a simple correlational method. The population comprised all 58 fifth-grade students of SD Inpres 48 Kabupaten Sorong, with 50 students selected as the sample through purposive sampling. Data were collected using a parental guidance questionnaire validated through the Pearson product-moment correlation test, and documentation of end-of-semester report card scores across all subjects. Data analysis employed simple linear regression and Pearson correlation. The results revealed a significant positive effect of parental guidance on student learning outcomes, with a correlation coefficient of r = 0.681 and a coefficient of determination R² = 0.464, indicating that 46.4% of the variance in student learning outcomes was accounted for by parental guidance. The regression equation was Ŷ = 34.27 + 0.56X. These findings underscore the critical role of parental involvement in supporting children’s academic achievement and recommend that schools implement structured parenting programs to empower parents in guiding their children’s learning at home.